Heterogeneidade enunciativa, gestão de vozes e orientação argumentativa no relatório da Comissão Nacional da Verdade do Brasil - Jaqueline Aparecida Nogueira (2022)
The general objective of this research is to analyze the dialogical marks of the discursive construction of the National Truth Commission Report, a collegiate responsible for investigating serious human rights violations committed between 1946 and 1988 in Brazil. Specifically, we aim to (i) characterize the corpus as a social practice, considering the concrete conditions of its production; (ii) relate the act of telling about oneself to its dialogical and memorial dimension; (iii) identify the presence of speakers/enunciators in the corpus and analyze their responsibilities and enunciative postures; (iv) analyze the role of the enunciative functioning and the management of the internal dialogism of points of view in the corpus within an argumentative problem; (v) investigate the sociodiscursive imaginaries moved from the materialization of points of view in the corpus and; (vi) to assess the extent to which the discursive construction of the report, especially with regard to narrative and enunciative procedures, guides the argumentative aims that defend the thesis of a historical truth about authoritarian periods. The theoretical-methodological basis focused on Mikhail M. Bakhtin (2009, 2011, 2015), Alain Rabatel (2016), Wander Emediato de Souza (2001, 2013, 2019), José Luiz Fiorin (2015), Ruth Amossy (2018), Patrick Charaudeau (2010, 2012a, 2012b; 2013, 2015) and in Jacqueline Authier-Revuz (1990, 2004, 2008). Initially, we present the report and its contexts of reference and appearance, we discuss the role of life narratives and testimonies in the material, we analyze the enunciative aspects, verifying the characteristics of speakers and enunciators and the marks of subjectivity in the planes of expression of the modal subject. Still on the enunciative level, we seek to understand the interactional dialogism of points of view and its relevance in the constitution of the report and its evidential sources, as well as the different enunciative postures represented by the speakers and enunciators staged in the text. Next, we analyze the argumentative aspects, focusing on their influence on the interactional management of points of view, such as the disposition and accountability of speakers and enunciators throughout the material and the argumentative schemes with demonstrative and/or persuasive intent present. Finally, we investigate the universe of beliefs moved through the points of view represented in the corpus. The results pointed to marks of dialogism in autodialogical and heterodialogical constructions, through which the witnesses exchanged the social and enunciative roles exercised in the past to the act of enunciation concretized by telling their experiences during the military period. We identified the illustration, the example and the analogy as the main argumentative strategies moved by the main speaker, in addition to the enunciative organization itself. In the analyzed samples, we found that the group belonging to the victims represented the Imaginaries of the Revolution, registered in the Imaginary of Popular Sovereignty, while the group belonging to the repressive agents represented the Imaginaries of Foreign Superiority, War and Absolute Power of Repressive Forces before civil society. In general, we found that the truth about the military period was presented to readers through evidential traits and modalities in a predominantly objective discourse.